THU0398 Observational Study on The Quality of Life of Italian Axial Spondyloarthritis Patients (QUASAR): Baseline Data. (15th July 2016) - Olivieri, I.; D'Attino, R.M.; Gualberti, G.; Merolla, R.
Abstract : Background: Quality of Life (QoL) is reduced in patients (pts) with axial spondyloarthritis (axSpA) who suffer from pain, stiffness and fatigue in their most productive years of life. Currently, data on QoL and impact on daily activities in axSpA pts classified according to the ASAS criteria are limited. No medical research in Italy has been conducted in AxSpA pts Objectives: To assess the evolution of QoL in pts suffering from axSpA over a 12-month period and disease impact on daily life activities Methods: QUASAR is a multicenter, longitudinal, observational study on adult axSpA pts in Italy. This interim analysis reports baseline data. Inclusion criteria were diagnosis of axSpA (either non radiographic [nr-axSpA] or ankylosing spondylitis [AS]) based on the ASAS classification criteria and ability to understand and complete the questionnaires. The following clinical parameters were recorded: CRP, HLA-B27, pain, stiffness, disease activity (BASDAI and ASDAS), Patient and Physician Global Assessment (PtGA/PGA), comorbidities and treatment. Subjects were asked to complete the ASQoL, WPAI, MARS, EQ-5D questionnaires and a VAS on satisfaction with the treatment during routine visits. Descriptive statistics (mean±Standard Deviation [SD] or frequencies) are presented for baseline clinical characteristics, disease activity and QoL. Mann-Whitney test, t-test, χ 2 were used to calculate differences between pts groups Results: A total of 512 pts (mean age 47.8±13.1 years; males 62.1%) were enrolled. 19% had a family history of SpA and 21% of psoriasis. 97 pts (18.9%) had a diagnosis of nr-axSpA. 246 (61.5%) subjects out of the 400 typed were HLA-B27 positive (48.7% and 62.7% of nr-axSpA and AS pts, respectively). Time to diagnosis since symptom onset was 5.4±2.9yrs for all pts, 3.8±3.1yrs for nr-axSpA and 5.8±2.8yrs for AS pts. 59.8% of nr-axSpA and 58.3% of AS pts had pain at the first visit. Low back pain was the most frequent type (73.3% of all pts) followed by cervical pain (35%) and dorsal pain (23.3%). 52.6% of nr-axSpA and 56.1% AS pts had morning stiffness. The following table shows the baseline demographic and characteristics of the pts involved in QUASAR: Extra Articular Manifestations (EAM) were as follows: psoriasis 17.6%, uveitis 15.8%, ulcerative colitis (UC) 4.1% and Crohn's disease 6.5%. EAMs were present in 24.7% and 15.9% (psoriasis), 15.5% and 15.9% (uveitis), 5.2% and 3.9% (UC), 4.1% and 7.0% (Crohn's disease) of nr-axSpA and AS pts Conclusions: QUASAR is the first prospective Italian study with a large sample size that reports an overall similar burden of disease in nr-axSpA and AS patients, documented by pain, CRP, PGA/PtGA, BASDAI, ASDAS, ASQOL, and EQ-5D VAS. Our data support the importance of early diagnosis and treatment of axSpA Acknowledgement: AbbVie funded the study, participated in its design/data collection/analysis/interpretation/writing publication Disclosure of Interest: I. Olivieri Grant/research support from: Abbvie, Bristol-Myers Squibb, Celgene, Janssen, Merck Sharp & Dohme, Novartis, Pfizer, Roche, UCB, Consultant for: Abbvie, Bristol-Myers Squibb, Celgene, Janssen, Merck Sharp & Dohme, Novartis, Pfizer, Roche, UCB, Speakers bureau: Abbvie, Bristol-Myers Squibb, Celgene, Janssen, Merck Sharp & Dohme, Novartis, Pfizer, Roche, UCB, R. M. D'Attino Employee of: Abbvie, G. Gualberti Employee of: Abbvie, R. Merolla Shareholder of: Abbvie, Employee of: Abbvie